Effect of sense of control on emotional experience and response in Chinese undergraduate students - Yao, Li; Guo, Yang; Zou, Xu; Zhang, Yutong; Zhang, Zhao; Xing, Suxuan (Frontiers in Psychology, 2025)
ObjectiveSense of control significantly influences emotional well-being. A lack of control over stressors induces negative affect, while control buffers the impact of stress in experimental animals. However, it is also unclear whether control or lack of control alters emotional response to subsequent stimuli in humans. Therefore, the present study aimed to investigate the effects of sense of control on the emotional experience and response to emotional stimuli in undergraduate students.MethodsIn Study 1, 488 participants were recruited to complete the questionnaires that included the Sense of Control Scale and Positive Affect and Negative Affect Scale (PANAS). In Study 2, 55 participants were randomly divided into a control group and a lack of control group. A concept identification task was used to manipulate the perceived control. The PANAS and a picture rating task were conducted before and after the manipulation.ResultsIn Study 1, The results revealed that the sense of control significantly predicted positive emotion (β = 0.28, p < 0.001) and negative emotion (β = −0.36, p < 0.001). In Study 2, compared to pre-test, the maintaining control group showed no significant changes in self-reported positive and negative emotion, nor in the valence ratings of emotion pictures after the manipulation. However, compared to pre-test, the lack of control group exhibited a decrease in self-reported positive emotion after the manipulation (p < 0.05), along with an increase in valence ratings for negative emotion pictures (p < 0.01). Additionally, the self-reported positive emotion in the lack of control group was lower than that in the control group after the manipulation (p < 0.05), while their valence ratings for negative emotion pictures were higher than those in the control group (p < 0.05). That is, maintaining control did not change the variables, while lack of control was associated with a decrease in positive affect and with valuing negative images as less negative.ConclusionControl did not significantly alter the emotional experience or response of individuals to emotional stimuli, whereas lack of control led to a decrease in positive affect and a decreased response to negative stimuli at the behavioral level.